INVESTIGATION INTO THE EFFECTS OF LOW SALINITY WATER ION COMPOSITIONS ON WETTABILITY AL TFRATION DURING FOAM FLOODING - SHABIB ASL, ABDOLMOHSEN (2016)
The ultimate goal of this work is to investigate the potential of a new hybrid EOR method termed Low Salinity Water Assisted Foam flooding (LSWAF). Typically. it consists of injecting Low Salinity Water (LSW) followed by an alternated injection of a Surfactant Aqueous Solution (SAS)and CO, gas. The selection ofLSW was based on its ability to produce signitlcant changes of rock wettability. While the SAS was made. so that it results in a considerable reduction of 1FT and produce foam that will remain considerably stable in the presence of oil under reservoir conditions. The selection of the best LSW and SAS followed a screening phase whereby formulations of different ion compositions and salinities were pn::pared and their performances were compared against each other.